1991
DOI: 10.1042/bj2740207
|View full text |Cite
|
Sign up to set email alerts
|

Electron-transfer steps involved in the reactivity of Hansenula anomala flavocytochrome b2 as deduced from deuterium isotope effects and simulation studies

Abstract: The L-lactate-flavocytochrome b2-ferricyanide electron-transfer system from the yeast Hansenula anomala was investigated by rapid-reaction techniques. The kinetics of reduction of oxidized flavocytochrome b2 by L-lactate and L-[2H]lactate were biphasic both for flavin and haem prosthetic groups and at all concentrations tested. The first-order rate constants of the rapid and slow phases depended upon substrate concentrations, a saturation behaviour being exhibited. Substitution of the C alpha-H atom by 2H was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…This is in marked contrast with the results of previous work on wild-type enzyme in which biphasic kinetics were observed for FMN reduction, at least at high lactate concentrations [12,[15][16][17]. For wild-type enzyme, it is known that the rapid phase corresponds to initial reduction of FMN and haem (with the slow phase being kinetically irrelevant in catalytic turnover of the enzyme) [12,[15][16][17]. The effect of the hinge-swap mutation on the rate of FMN reduction is small, with kcat for the mutant enzyme being only 2-to 3-fold lower than that for the wild-type enzyme.…”
Section: Stopped-flow Kinetic Analysiscontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in marked contrast with the results of previous work on wild-type enzyme in which biphasic kinetics were observed for FMN reduction, at least at high lactate concentrations [12,[15][16][17]. For wild-type enzyme, it is known that the rapid phase corresponds to initial reduction of FMN and haem (with the slow phase being kinetically irrelevant in catalytic turnover of the enzyme) [12,[15][16][17]. The effect of the hinge-swap mutation on the rate of FMN reduction is small, with kcat for the mutant enzyme being only 2-to 3-fold lower than that for the wild-type enzyme.…”
Section: Stopped-flow Kinetic Analysiscontrasting
confidence: 99%
“…A number of workers have previously described the origin of this biphasic behaviour which arises because each flavocytochrome b2 protomer requires three electrons for full reduction (i.e. each tetramer requires 12 electrons from six lactate molecules for full reduction) [12,[15][16][17]. These workers have shown that the rapid phase corresponds to the initial reduction of flavin and haem groups and the slow phase (which is kinetically irrelevant during catalytic turnover of the enzyme) corresponds to the entry of the third electron which is permitted because of interprotomer electron transfer [12,[15][16][17].…”
Section: Scheme 1 Catalytic Cycle Of Lactate Oxidation and Cytochromementioning
confidence: 99%
“…The reduction of the FMN and haem groups of wild-type and Y143F flavocytochromes b2 by L-lactate and L-[2-2H]lactate was monitored by stopped-flow spectrophotometry as described in the Materials and methods section. As noted in previous work [10,17,18], at high lactate concentrations biphasic traces were observed with the rapid phase corresponding to at least 80 % of the absorbance change (monophasic traces were observed at low lactate concentrations, as described in the Materials and methods section). It has been well documented that the rapid phase corresponds to the initial reduction of FMN and haem groups by one L-lactate molecule, whereas the slow phase corresponds to entry of a third electron into the flavocytochrome b2 promoter [10,18,19].…”
Section: Stopped-flow Kinetic Parameterssupporting
confidence: 75%
“…characteristics of the isolated flavocytochrome b2 flavin domain and the intact, native enzyme is seen in stopped-flow experiments. FMN in the isolated domain is reduced as a single exponential process, as found also in the dehaemo-enzyme [14], whereas FMN reduction in the intact holoenzyme is biphasic [15,16,18,19]. The slow phase has been attributed to an intramolecular redistribution of electrons after haem reduction (Figure 3a).…”
Section: Discussionmentioning
confidence: 63%
“…Although monophasic kinetics were observed for fully active flavin domain we found that enzyme which had lost activity exhibited biphasic behaviour; however, this is most likely due to heterogeneity in the enzyme. The monophasic reduction of fully active enzyme contrasts dramatically with the behaviour of wild-type flavocytochrome b2 which exhibits biphasic FMN reduction, notably at high concentrations of lactate [15,16,18,19]. The fast phase corresponds to the initial two-electron reduction of FMN but subsequent reduction of the haem and interprotomer electron transfer Table 2 Steady-state kinetc parametws and 2H kinetic Isotope effects for the Isolated flavin domain and intact, wild-type flavocytoochrome b2…”
Section: Steady-state Kinetic Analysismentioning
confidence: 99%